1998
DOI: 10.1007/s007020050068
|View full text |Cite
|
Sign up to set email alerts
|

Brain insulin and insulin receptors in aging and sporadic Alzheimer's disease

Abstract: The search for the causes of neurodegenerative disorders is a major theme in brain research. Acquired disturbances of several aspects of cellular metabolism appear pathologically important in sporadic Alzheimer's disease (SDAT). Among these brain glucose utilisation is reduced in the early stages of the disease and the regulatory enzymes important for glucose metabolism are reduced. In the brain, insulin, insulin-like growth factors and their receptors regulate glucose metabolism and promote neuronal growth. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
406
2
11

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 682 publications
(443 citation statements)
references
References 57 publications
8
406
2
11
Order By: Relevance
“…Conversely, dysfunctional IR mutants that manifest insulin resistance syndrome in clinic, or pharmacological inhibition of the receptor activities prevent ADDL removal and promote its further aggregation. These results provide compelling evidence linking insulin resistance to A␤ abnormality, strongly supporting the hypothesis that dysfunctional CNS insulin or IGF-1 signaling may significantly contribute to the onset and progression of AD pathology (40,41,61,62,85,86).…”
Section: Discussionsupporting
confidence: 63%
“…Conversely, dysfunctional IR mutants that manifest insulin resistance syndrome in clinic, or pharmacological inhibition of the receptor activities prevent ADDL removal and promote its further aggregation. These results provide compelling evidence linking insulin resistance to A␤ abnormality, strongly supporting the hypothesis that dysfunctional CNS insulin or IGF-1 signaling may significantly contribute to the onset and progression of AD pathology (40,41,61,62,85,86).…”
Section: Discussionsupporting
confidence: 63%
“…However, it is known that enriched environment in the adult increases the expression of other factors that are potentially important for visual system development (neurotrophins, signal transduction molecules, NMDA receptors, GAD 65, CREB, and many others) (Molteni et al, 2002) and, in particular, increases IGF-I expression (Carro et al, 2000;Thoenen and Sendtner, 2002). IGF-I receptors are present in the occipital cortex (Frolich et al, 1998), and IGF-I could therefore influence the expression of molecules relevant for visual cortical plasticity such as nerve growth factor and BDNF itself. We are aware of the complexity of the cellular and molecular changes potentially induced by enriched environment in the developing visual cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has begun to uncover the underlying mechanisms of insulin signaling dysfunction in AD. Clinically, there is a higher density of insulin receptors in the brain of patients with AD compared to control subjects, possibly reflecting upregulation of the receptor in an attempt to compensate for the decreased functionality of insulin (Frolich et al, 1998). By contrast, some studies reported decreased insulin receptor binding in individuals with AD in comparison with age‐matched control (Arnold et al, 2018; Rivera et al, 2005; Steen et al, 2005).…”
Section: Lifestyle Associations and Interventions For Aging And Admentioning
confidence: 99%